2006
DOI: 10.1128/aem.02119-05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Group A Rotaviruses in Water Sources and Selected Raw Vegetables in Southern Africa

Abstract: Group A rotaviruses (RVs) are the most important cause of acute viral gastroenteritis in infants and young children. In this study raw and treated drinking water supplies at plants in two geographic areas, as well as selected irrigation water and corresponding raw vegetables in three regions of southern Africa, were screened for the presence of RVs using molecular techniques. Group A RVs were detected in 11.8% of partially treated and 1.7% of finally treated drinking water samples and in 14% of irrigation wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 52 publications
(66 reference statements)
8
56
1
1
Order By: Relevance
“…In some studies, rotavirus strain characteristics revealed in sewage and contaminated surface basins were closely mirroring the strains normally responsible for the majority of infant disease cases [41,49], but this may actually be true particularly for countries with lower sanitation where disposal of adult stools and children diapers is not kept separated. A preliminary comparison between G-and Ptypes of rotavirus detected in either sewage samples or feces of children with diarrhea in Italy in 2010-2011 is reported in Figures 1 and 2, showing similar yet not identical distribution of viral strains.…”
Section: Rotavirus and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, rotavirus strain characteristics revealed in sewage and contaminated surface basins were closely mirroring the strains normally responsible for the majority of infant disease cases [41,49], but this may actually be true particularly for countries with lower sanitation where disposal of adult stools and children diapers is not kept separated. A preliminary comparison between G-and Ptypes of rotavirus detected in either sewage samples or feces of children with diarrhea in Italy in 2010-2011 is reported in Figures 1 and 2, showing similar yet not identical distribution of viral strains.…”
Section: Rotavirus and The Environmentmentioning
confidence: 99%
“…Rotavirus contamination of surface water may also end up in other food chains, including vegetables and soft fruit, correlated with irrigation. Although virus concentration may be lower on leaves and fruit skin, this type of food is a potential risk and has in fact been sporadically involved in outbreaks [32,49]. Conditions for exceptional virus spread and large outbreaks may be generated by major natural events like flood and earthquakes [58].…”
Section: Rotavirus Epidemic Outbreaksmentioning
confidence: 99%
“…This is the basis for the high incidence of rotavirus gastroenteritis, especially in winter months, when their stability, due to relative humidity and temperature conditions, is further increased (1,6). It has been shown that raw food, untreated water, treated water, and irrigation water can represent possible sources of rotaviral gastroenteritis outbreaks (6,30). As an example, in a recent study performed in southern Africa, the presence in irrigation waters of multiple rotavirus types (G1, G2, G8, and G9) was confirmed by using type-specific RT-PCR (30).…”
mentioning
confidence: 99%
“…It has been shown that raw food, untreated water, treated water, and irrigation water can represent possible sources of rotaviral gastroenteritis outbreaks (6,30). As an example, in a recent study performed in southern Africa, the presence in irrigation waters of multiple rotavirus types (G1, G2, G8, and G9) was confirmed by using type-specific RT-PCR (30). In addition, swine or cattle slurry deposited in fields could contain animal rotavirus types, which could pass via runoff water into freshwater and later be transmitted to humans (6), causing illnesses of various severities (16).…”
mentioning
confidence: 99%
“…Group A rotaviruses have been detected in untreated and treated drinking-water samples in Southern Africa (Van Zyl et al, 2006). While detection of both HAV and RVs was observed to be confined to the upstream stretch of the river compared to the downstream (P<0.05), occurrence of both viruses tended to be sporadic (P>0.05).…”
Section: Discussionmentioning
confidence: 98%